2020
DOI: 10.2147/jpr.s269329
|View full text |Cite
|
Sign up to set email alerts
|

<p>Challenges of Misdiagnosis and Suboptimal Treatment of Persistent Idiopathic Facial Pain and Atypical Odontalgia: A Retrospective Multi-Centric Cross-Sectional Investigation</p>

Abstract: Purpose To explore the challenges faced in the diagnosis and treatment of atypical odontalgia (AO) and other persistent idiopathic facial pain (PIFP). Patients and Methods This retrospective multi-centric cross-sectional study utilized clinical information (eg, clinical manifestations, history of consultations and treatments prior to correct diagnoses) from patients’ medical records. Their economic parameters were also extracted from medical insurance databases. Each va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“… 5 A retrospective multi-centric cross-sectional study including a total of 394 patients found that the average diagnostic delay of AO was much longer and costed more than patients with any other persistent idiopathic facial pain (PIFP). 6 When patients are misdiagnosed, they often take drugs that do not work, sometimes even undergo several unnecessary surgeries which does not alleviate but rather aggravate the pain. This rare clinical challenge, as one of the representative chronic orofacial pains, 7 result in unsatisfactory treatment outcomes and severely affect patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 A retrospective multi-centric cross-sectional study including a total of 394 patients found that the average diagnostic delay of AO was much longer and costed more than patients with any other persistent idiopathic facial pain (PIFP). 6 When patients are misdiagnosed, they often take drugs that do not work, sometimes even undergo several unnecessary surgeries which does not alleviate but rather aggravate the pain. This rare clinical challenge, as one of the representative chronic orofacial pains, 7 result in unsatisfactory treatment outcomes and severely affect patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Analgesics were avoided in this study to prevent interference with the results. After taking duloxetine, pain was relieved by an average of 5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days after beginning treatment. These results are consistent with the results reported by Yasuda et al's study 29 which reported the pain relief efficacy of duloxetine in patients with diabetic neuropathy (DNP) in the first week of administration.…”
mentioning
confidence: 99%
“…The clinical patients, we included mainly came from the department of oral medicine, department of oral pathology and maxillofacial surgery, and oral medicine was indicated as optimal when compared to other dental specialties ( Brailo et al., 2006; Fattori et al., 2019; Li et al., 2015; Netto et al., 2011). The data in clinical settings revealed that BMS patients had a high demand for medical consultation and further management (Xiao et al., 2020). In addition to dental department, a retrospective study found that BMS patients also sought help from multiple clinics and other medical specialties such as otorhinolaryngology, dermatology, neurosurgery, and anesthesia departments (Freilich et al., 2020; Xiao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the financial burden of this disease could not be easily described. It was reported the cost of correct diagnosis was 1,570.7$ for patients with atypical odontalgia and 1,316.8$ for those who had persistent idiopathic facial pain (Xiao et al, 2018). Breckons's study showed that chronic orofacial pain patients' out‐of‐pocket costs were 463.5$ and indirect costs were 1,728.7$ for medical care every six months (Breckons et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation